2015
DOI: 10.1590/1982-370301572013
|View full text |Cite
|
Sign up to set email alerts
|

Adolescência e Tendência Antissocial: o Rap como Expressão de uma Privação Emocional

Abstract: O presente estudo objetiva refletir sobre a tendência antissocial no adolescente/jovem, por meio da análise do conteúdo descrito nas letras de músicas de rap brasileiro, as quais em geral surgem carregadas de revolta, inconformismo, denúncias sociais e esperança. A pesquisa se caracteriza como exploratória, documental e qualitativa. Para tanto, foi realizada análise de conteúdo das letras, e posterior discussão embasada na teoria de Donald Woods Winnicott, buscando nos trechos das músicas indícios referentes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
2
2
0
2
Order By: Relevance
“…On the other hand, it appears that the JO group has greater differences, with the highest concentration in the 16-year-old group, with a significant difference. These data corroborate the findings in the literature which indicate that the majority of teenagers undergoing correctional measures is mostly concentrated in the age group between 15 and 17 years old (Paula & Assumpção, 2013;Silva & Milani, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, it appears that the JO group has greater differences, with the highest concentration in the 16-year-old group, with a significant difference. These data corroborate the findings in the literature which indicate that the majority of teenagers undergoing correctional measures is mostly concentrated in the age group between 15 and 17 years old (Paula & Assumpção, 2013;Silva & Milani, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The analysis of the gender category shows the Control and DV groups quite similar and the JO group with a greater number of male participants, with a significant difference (p-value = 0.0002). This characterization also seems to confirm the results of studies on the profile of adolescent offenders, which indicate that most of them are male (Paula & Assumpção, 2013;Silva & Milani, 2015). In contrast, the literature indicated that the distribution of victims of domestic violence in terms of gender is more equal (Malta et al, 2017;.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Para melhor compreensão da magnitude dessas consequências, basta observar o elevado número de jovens envolvidos com algum tipo de criminalidade, somente no ano de 2017 mais de 24 mil adolescentes se encontravam em conflito com a lei (IBGE; SDH, 2017), e para observar a construção deste cenário, é essencial olhar para a origem da questão, na qual em sua maioria, tratam-se de famílias monoparentais de baixa renda e com mães sem nenhum suporte que um companheiro ou família deveriam propiciar, para que assim desfrutassem de uma maternidade sem complicações (SILVA; MILANI, 2015). Ao longo da vida, as crianças aprendem que a comida é um meio para aliviar as tensões, uma vez que desde o seu nascimento foram ensinadas a receber o alívio pela boca através da mamada, dedos na boca e até mesmo pelas chupetas.…”
Section: Resultsunclassified
“…A privação emocional é o gerenciamento de emoções negativas que causam privação sentimental e consequentemente pode causar deficiência transitória da libertação do hormônio do crescimento. Dependendo do momento e da intensidade na vida desse adolescente em que a privação se inseriu, poderão se desenvolver diferentes respostas (26) .…”
Section: Discussionunclassified